Endothelial Senescence and Chronic Fatigue Syndrome, a COVID-19 Based Hypothesis - Sfera, Adonis; Osorio, Carolina; Zapata Martín del Campo, Carlos M.; Pereida, Shaniah; Maurer, Steve; Maldonado, Jose Campo; Kozlakidis, Zisis (Frontiers in Cellular Neuroscience, 2021)
Abstract Myalgic encephalomyelitis/chronic fatigue syndrome is a serious illness of unknown etiology, characterized by debilitating exhaustion, memory impairment, pain and sleep abnormalities. Viral infections are believed to initiate the pathogenesis of this syndrome although the definite proof remains elusive. With the unfolding of COVID-19 pandemic, the interest in this condition has resurfaced as excessive tiredness, a major complaint of patients infected with the SARS-CoV-2 virus, often lingers for a long time, resulting in disability and poor life quality. In a previous article, we hypothesized that COVID-19-upregulated angiotensin II triggered premature endothelial cell senescence, disrupting the intestinal and blood brain barriers. Here, we hypothesize further that post-viral sequelae, including myalgic encephalomyelitis/chronic fatigue syndrome, are promoted by the gut microbes or toxin translocation from the gastrointestinal tract into other tissues, including the brain. This model is supported by the SARS-CoV-2 interaction with host proteins and bacterial lipopolysaccharide. Conversely, targeting microbial translocation and cellular senescence may ameliorate the symptoms of this disabling illness.